2005
DOI: 10.2202/1542-6580.1250
|View full text |Cite
|
Sign up to set email alerts
|

iso-Amyl Acetate Synthesis by Catalytic Distillation

Abstract: With ever-growing environmental concerns, petrochemical and fine chemical industries face an omnipresent issue in recovering dilute acetic acid from its aqueous solutions. Catalytic distillation holds an ascendancy over conventional physical separation methods such as distillation and extraction. Distillation is associated with the high costs involved in vaporising the more volatile water that exists in high proportions and possesses a high latent heat of vaporisation. Extraction is limited in view of the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Reactive distillation (RD) is one of the emerging technologies that has an extremely attractive potential as a process alternative for carrying out equilibrium limited liquid phase chemical reactions (Saha and Sharma, 1996;Saha et al 2005). It is a unit operation which combines simultaneous chemical reaction and multi-component distillation in the same vessel in a single step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive distillation (RD) is one of the emerging technologies that has an extremely attractive potential as a process alternative for carrying out equilibrium limited liquid phase chemical reactions (Saha and Sharma, 1996;Saha et al 2005). It is a unit operation which combines simultaneous chemical reaction and multi-component distillation in the same vessel in a single step.…”
Section: Introductionmentioning
confidence: 99%
“…We are also developing a detailed knowledge of the repeated use of this catalyst to provide experimental parameters to aid in the design of a reactive-distillation column upon which we are already embarked. The design is based upon a previous successful reactive-distillation column (RDC) rig used for esterifications (Saha and Sharma, 1996;Saha et al 2005) but will require significant modification to be compatible with the quite different physico-chemical demands of alkene epoxidations. In this paper we will highlight some batch experimental studies for epoxidation of alkene catalyzed by polymer supported Mo(VI) complex.…”
Section: Introductionmentioning
confidence: 99%
“…RD has also been recommended for the esterifi cation of isoamyl acetate 4, 18-20 , which is widely used as an additive to fl avor processed food and beverages. In an experimental investigation, the conversion of acetic acid with RD was reported to reach 69.5% as compared with the 18.2% achieved by a conventional batch reactor 18 . Patil and Kulkarni 19 determined the esterifi cation reaction kinetics of acetic acid with isoamyl alcohol in a batch reactor.…”
Section: Introductionmentioning
confidence: 92%
“…Besides the basic reaction research, different processes were designed to synthesis i-AmAc. Saha et al [13] provided a CRD process for the synthesis of i-AmAc via the esterification of i-AmOH and HAc, and a cation exchange resin catalyst named Purolite CT-175 was used in the catalytic reactive section. Ali et al [14] compared the CRD process with the conventional reactor-separator process on synthesis of i-AmAc, which confirmed that the CRD process showed advantages on both energy consumption and capital cost.…”
Section: Introductionmentioning
confidence: 99%